2021
DOI: 10.1038/s41598-021-02990-w
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of uniform linearly-arranged micro-droplets entrapping DNA and living cells through water/water phase-separation

Abstract: Living cells maintain their lives through self-organization in an environment crowded with a rich variety of biological species. Recently, it was found that micro-droplets containing biomacromolecules, which vary widely in size, are generated accompanied by water/water phase-separation by simple mechanical mixing of an aqueous solution with binary polymers. Here, we report that cell-sized droplets of nearly the same size are generated as a linear array within a glass capillary upon the introduction of a binary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…This pattern, emerging from the phase separation of two types of hydrophilic polymers in water within a capillary, organizes itself. 31,32 In this present study, we demonstrate that a periodic alignment of binary microdroplets, each surrounded by a different polymer solution, arises from the phase separation of an aqueous tripolymer solution in a capillary. Recently, in the studies concerning coacervate formation, generation of various specific spatial patterns with polydispersity have been reported.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…This pattern, emerging from the phase separation of two types of hydrophilic polymers in water within a capillary, organizes itself. 31,32 In this present study, we demonstrate that a periodic alignment of binary microdroplets, each surrounded by a different polymer solution, arises from the phase separation of an aqueous tripolymer solution in a capillary. Recently, in the studies concerning coacervate formation, generation of various specific spatial patterns with polydispersity have been reported.…”
mentioning
confidence: 51%
“…Conversely, our recent findings reveal the spontaneous alignment of uniformly sized microdroplets within a quasi-one-dimensional confinement (quasi-1D). This pattern, emerging from the phase separation of two types of hydrophilic polymers in water within a capillary, organizes itself. , In this present study, we demonstrate that a periodic alignment of binary microdroplets, each surrounded by a different polymer solution, arises from the phase separation of an aqueous tripolymer solution in a capillary. Recently, in the studies concerning coacervate formation, generation of various specific spatial patterns with polydispersity have been reported. , It is particularly notable that the periodic pattern formation of our study occurs in a thermodynamically closed system, which is in contrast to the pattern formation observed in thermodynamically open systems, such as the reaction-diffusion system responsible for Turing patterns. In essence, the spatial periodic pattern in our system is kinetically stable, persisting without the need for a continuous input of energy or materials, distinguishing it from the dynamics of patterning in reaction-diffusion systems.…”
mentioning
confidence: 99%
“…Activated T cells were detected and analyzed by a microfluidic system, and the TCR was cloned. The technique is based on T-cell functional analysis, which reduces nonspecific findings [ 250 , 251 ]. However, the number of T cells in each analysis was limited, and the system complexity was high.…”
Section: Introductionmentioning
confidence: 99%
“…To solve these issues, we have previously reported that ATPS of confined polymer blends can be utilized for the size control of w/w droplets. [ 31 ] The phase separation of PEG/DEX solution inside a glass capillary produces cell‐sized droplets with approximately uniform size through spinodal decomposition [ 32 ] within the confinement of quasi‐1D. We used this ATPS method to produce uniform cell‐sized microgels.…”
Section: Introductionmentioning
confidence: 99%